Assessing the emergence and reliability of cognitive decline over the life span in Fisher 344 rats using the spatial water maze - Guidi, Michael; Kumar, Ashok; Rani, Asha; Foster, Thomas C. (Frontiers in Aging Neuroscience, 2014)
The spatial water maze is routinely used to investigate hippocampal-dependent spatial memory and the biological mechanisms that underlie variability in cognitive decline during aging. The utility of the task for repeated testing in order to examine the trajectory of cognitive decline and to prescreen animals prior to therapeutic interventions maybe limited due to carryover effects of repeated training. The current study examines the role of carryover effects, as well as the reliability of individual differences, in determining age-related impairment on episodic and reference memory versions of the water maze task. Results indicate that impaired acquisition of episodic spatial information emerges in middle-age and the propensity for impairment increases with advancing age. While learning was variable across animals, acquisition deficits for episodic information were reliable across training sessions in middle-age and aged rats. A significant impairment in the 24~h retention of episodic spatial information was observed in aged animals. When animals were trained to the same location (i.e., reference memory), an impairment was limited to the rate of acquisition in aged animals. However, with continued training, all aged animals were able to acquire a reference memory and no age differences were observed in the 24~h retention of a spatial reference memory. Together, the results point to a progressive impairment in episodic spatial memory with advancing age and suggest that tests of episodic spatial memory are reliable and more sensitive than reference memory for detecting cognitive decline.